Rethinking Mental Language: Toon’s Fictionalism and its Philosophical Roots - Srivastava, Ayush (Problemos, 2025)
Book Review: Mind as Metaphor: A Defence of Mental Fictionalism. Adam Toon. Oxford University Press, 20 April 2023. (https://doi.org/10.1093/oso/9780198879626.001.0001, 160 pp. ISBN: 9780198879626)
Keywords: Cartesianism; Mental Fictionalism; Metaphors; Representational theory; Ryle